Adverse respiratory effects in rats following inhalation exposure to ammonia: respiratory dynamics and histopathology. (2nd January 2017) - Perkins, Michael W.; Wong, Benjamin; Tressler, Justin; Rodriguez, Ashley; Sherman, Katherine; Andres, Jaclynn; Devorak, Jennifer; L. Wilkins, William; Sciuto, Alfred M.
Abstract: Acute respiratory dynamics and histopathology of the lungs and trachea following inhaled exposure to ammonia were investigated. Respiratory dynamic parameters were collected from male Sprague–Dawley rats (300–350 g) during (20 min) and 24 h (10 min) after inhalation exposure for 20 min to 9000, 20, 000, and 23, 000 ppm of ammonia in a head-only exposure system. Body weight loss, analysis of blood cells, and lungs and trachea histopathology were assessed 1, 3, and 24 h following inhalation exposure to 20, 000 ppm of ammonia. Prominent decreases in minute volume (MV) and tidal volume (TV) were observed during and 24 h post-exposure in all ammonia-exposed animals. Inspiratory time (IT) and expiratory time (ET) followed similar patterns and decreased significantly during the exposure and then increased at 24 h post-exposure in all ammonia-exposed animals in comparison to air-exposed controls. Peak inspiratory (PIF) and expiratory flow (PEF) significantly decreased during the exposure to all ammonia doses, while at 24 h post-exposure they remained significantly decreased following exposure to 20, 000 and 23, 000 ppm. Exposure to 20, 000 ppm of ammonia resulted in body weight loss at 1 and 3 h post-exposure; weight loss was significant at 24 h compared to controls. Exposure to 20, 000 ppm of ammonia for 20 min resulted in increases in the total blood cell counts of white blood cells, neutrophils, and platelets at 1, 3, and 24 h post-exposure. Histopathologic evaluation of the lungs and trachea tissue of animals exposed to 20, 000 ppm of ammonia at 1, 3, and 24 h post-exposure revealed various morphological changes, including alveolar, bronchial, and tracheal edema, epithelial necrosis, and exudate consisting of fibrin, hemorrhage, and inflammatory cells. The various alterations in respiratory dynamics and damage to the respiratory system observed in this study further emphasize ammonia-induced respiratory toxicity and the relevance of efficacious medical countermeasure strategies.